Is Shame Hallucinogenic? - McCarthy-Jones, Simon (Frontiers in Psychology, 2017)
Research into the causes of ‘hearing voices’, formally termed auditory verbal hallucinations (AVH), has primarily focused on cognitive mechanisms. A potentially causative role for emotion has been relatively neglected. This paper uses historical and contemporary case studies of AVH to tentatively generate the hypothesis that shame can be a causal factor in the onset of AVH. Other sources of support for the generation of this hypothesis are then sought. First, evidence is examined for a role of shame in the aetiology of post-traumatic stress disorder, a condition that is characterised by phenomena related to AVH (intrusions and dissociation) and in which a substantial minority of sufferers report AVH. Second, the effect on AVH of a psychological therapy specifically designed to counteract shame (Compassion Focused Therapy) is noted. The hypothesis generation process is then expanded to propose mechanisms that could mediate a relation between shame and AVH. It is proposed that employing absorbed or avoidant strategies to deal with shame may lead to AVH through mediating mechanisms such as rumination, suppression, and dissociation. Evolutionary reasons for a relation between shame and AVH are also proposed, including that AVH may be an evolved mechanism to encourage self-protective behaviours in the wake of trauma. It is concluded that existing research supports the generation of this paper’s hypothesis, which is now worthy of dedicated empirical testing.